Searching for easy indicators for degraded tropical pastureland soils - Tam, Kristen (International Livestock Research Institute, 2024)
There’s a lack of research in grasslands and how to identify degraded soils, or to protect them. Biological differences between ‘good’ and “poor” soils are also hard to see. ‘Research on soil health indicators such as penetration rate have been conducted in other places, but there have been very few experiments in tropical soils. The soils in western Kenya are millions of years old while soils in Europe are 10-20 thousand, how they become degraded will differ greatly!’ said Leitner. Lab-based chemical and biological analysis methods are inaccessible, time consuming and expensive for communities to use. Methods must also be specifically tailored to the very old and clay filled soils in western Kenya. Soil matters for the people, plants and animals who depend on it. For instance, if water doesn’t infiltrate well, it results in limited water availability for plants and runoff can also lead to erosion and loss of soil nutrients.